2014
DOI: 10.1590/s0104-77602014000100018
|View full text |Cite
|
Sign up to set email alerts
|

Miniestaquia de Eucalyptus benthamii: efeito do genótipo, AIB, zinco, boro e coletas de brotações

Abstract: RESUMO:Objetivou-se avaliar o enraizamento adventício em miniestacas de Eucalyptus benthamii em relação ao genótipo, concentrações de Zn e B, coleta de brotações e aplicação de AIB. As brotações foram oriundas de minicepas fertirrigadas com soluções nutritivas variando nas concentrações de Zn e B (S1 -isento de Zn e B, S2 -0,5 mg L -1 de Zn, S3 -0,5 mg L -1 de B, S4 -0,5 mg L -1 de Zn e B, S5 -1,0 mg L -1 de Zn e B, S6 -2,0 mg L -1 de Zn e B). A região basal da miniestaca foi imersa durante 10 s em solução con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 15 publications
0
8
0
18
Order By: Relevance
“…The average, maximum and minimum temperatures of the day, in given time-intervals, are parameters that might be considered in establishing an optimal range. Brondani et al (2014) reported that Eucalyptus benthamii minicuttings exhibited increased callus formation on their basal region with high temperatures, indicating the influence of maximum temperatures in rhizogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The average, maximum and minimum temperatures of the day, in given time-intervals, are parameters that might be considered in establishing an optimal range. Brondani et al (2014) reported that Eucalyptus benthamii minicuttings exhibited increased callus formation on their basal region with high temperatures, indicating the influence of maximum temperatures in rhizogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The four combinations conducted for cleft grafting (scion/rootstock: K. The solution pH was adjusted to 5.8 at 25°C with HCl or NaOH, both at 1.0 M. Modified from Brondani et al (2014).…”
Section: Cleft Graftingmentioning
confidence: 99%
“…A critical factor in determining adventitious rooting was the application of a nutrient solution with at least 50% of the macro and micronutrients concentrations proposed by Brondani et al (2014) (Table 3). Moreover, the application of IBA improved adventitious rooting.…”
Section: Air Layeringmentioning
confidence: 99%
See 1 more Smart Citation
“…A redução no percentual de sobrevivência entre as fases de casa de vegetação e casa de sombra são tidas como normais para espécies subtropicais de Eucalyptus (BRONDANI et al, 2014). Relata-se que, por vezes, a sobrevivência ao fim da casa de vegetação pode reduzir a níveis de perda total do material (BRONDANI et al, 2010a;.…”
Section: Figura 2 Sobrevivência De Miniestacas De E Dunnii Avaliadaunclassified